2021
DOI: 10.3390/met11121948
|View full text |Cite
|
Sign up to set email alerts
|

WAAM-Fabricated Laminated Metal Composites

Abstract: Laminated metal composites are a promising design since the hybrid design enables superior and tailorable material properties compared with bulk material. The article introduces for the first time, laminated metal composites consisting of multiple bilayers of alternating layers of ductile and high-strength steel processed by wire arc additive manufacturing (WAAM). The layup of the laminated metal composites is built up by alternating deposits made of ductile steel and high-strength steel type wires. Governing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Therefore, it seems essential to characterise the up-to-date peening processes and review their effects on the properties of a surface layer of metal alloys. Currently, the additive manufacturing of metallic components is considered rather modern when it comes to manufacturing technology [ 1 , 2 , 3 ]. However, the surface of additively constituted parts needs to be finished, and in particular, shot peening can be easily employed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it seems essential to characterise the up-to-date peening processes and review their effects on the properties of a surface layer of metal alloys. Currently, the additive manufacturing of metallic components is considered rather modern when it comes to manufacturing technology [ 1 , 2 , 3 ]. However, the surface of additively constituted parts needs to be finished, and in particular, shot peening can be easily employed.…”
Section: Introductionmentioning
confidence: 99%
“…Spalek et al [3] investigated laminated metal composites consisting of multiple bilayers of alternating layers of ductile and high-strength steel that were processed by WAAM for the first time. The findings demonstrated that the mechanical properties of the laminated metal composites were significantly influenced by the dilution between unalloyed SG2 and X90 weld beads, leading to a similar range in hardness for both SG2 and X90 steel.…”
Section: Contributionsmentioning
confidence: 99%
“…Laminated metal composites (LMCs), consisting of multiple bilayers of alternating layers of ductile and high-strength steel, processed by WAAM using a computer code guided welding robot, were investigated in [166]. The WAAM LMCs, produced by RW, could be applied also in the marine industry.…”
Section: Future Developments Of Welded Joints In Marine Structuresmentioning
confidence: 99%